Significant Broadband Photocurrent Enhancement by Au-CZTS Core-Shell Nanostructured Photocathodes - Zhang, Xuemei (Sci Rep, 2016)
Copper zinc tin sulfide (CZTS) is a promising material for harvesting solar energy due to its abundance and non-toxicity. However, its poor performance hinders their wide application. In this paper gold (Au) nanoparticles are successfully incorporated into CZTS to form Au@CZTS core-shell nanostructures. The photocathode of Au@CZTS nanostructures exhibits enhanced optical absorption characteristics and improved incident photon-to-current efficiency (IPCE) performance. It is demonstrated that using this photocathode there is a significant increase of the power conversion efficiency (PCE) of a photoelectrochemical solar cell of 100% compared to using a CZTS without Au core. More importantly, the PCE of Au@CZTS photocathode improved by 15.8% compared to standard platinum (Pt) counter electrode. The increased efficiency is attributed to plasmon resonance energy transfer (PRET) between the Au nanoparticle core and the CZTS shell at wavelengths shorter than the localized surface plasmon resonance (LSPR) peak of the Au and the semiconductor bandgap.